“From the city of mango trees to the city of concrete”: study on urban public green leisure areas in Belém (Pará, Brazil) - Lobato, Flavio Henrique Souza; Hamoy, Juliana Azevedo; Bahia, Mirleide Chaar; Meguis, Thiliane Regina Barbosa; Mendes, Fabricio Lemos de Siqueira (Revista Brasileira de Ecoturismo (RBEcotur), 2023)
The Urban Public Green Areas (UPGA) in the Amazon represents a small environmental and cultural sample of different spaces and ways of traditional populations life’s and cities in the region. Although, such areas have been under pressure from urban expansion, and in some cases, they do not meet the citizens needs and use of these spaces for leisure. Thus, this research aimed to analyze the distribution, access and reduction of urban public green areas for leisure in Belém. The qualitative-quantitative methodology uses bibliographic and documental research, based on official data on demography and geolocation. The data were submitted to three indicators calculation, namely: Territorial Proportion of Vegetation Coverage Indicator, Vegetation Coverage per Inhabitant Indicator and, within UPGA scope, the Territorial Distribution of Leisure Spaces Indicator. As a result, it was possible to verify that Belém has been progressively losing green areas. In the reduction in UPGA, a significant difference in distribution was also identified, either due to the absence of quality spaces or due to inadequate infrastructure and access. In this way, the leisure practices and sociability in these spaces have been made impracticable, and the population has started to resort to other leisure experiences, which are often nature disconnected.